Liberalism, Liberal Egalitarianism or Communitarianism? - Fantoni, Wagner Facundo (2015)
Three philosophies have different proposals and pathways in the ethical field of the study and the solution of problems relating to justice: liberalism, liberal egalitarianism and communitarianism. His representatives are called respectively liberal, liberal-egalitarian and communitarian. In this paper, we intend to evaluate each of these philosophical lines, presenting their strengths and weaknesses, and to demonstrate that liberalism must be rejected  at  the  expense  of  liberal  egalitarianism  and  of  communitarianism.  These philosophies have more plausible ways of problem solving than the liberal way. Accordingly, the liberal egalitarianism and communitarianism not necessarily repel. On the contrary, they can be applied jointly, which will be demonstrated in this paper. This hypothesis is developed and confirmed in this paper through the survey and study of the relevant doctrine.